2006
DOI: 10.1071/ea04127
|View full text |Cite
|
Sign up to set email alerts
|

Vase treatments containing gibberellic acid do not increase longevity of cut Grevillea 'Sylvia' inflorescences

Abstract: The longevity of Grevillea ‘Sylvia’ inflorescences can be very short and is influenced by exposure to ethylene. Gibberellic acid has the potential to delay senescence in some cut flowers by acting as an anti-ethylene treatment. Gibberellic acid was therefore applied to Grevillea ‘Sylvia’ inflorescences in vase solutions to determine its effects on longevity. Treatments with gibberellic acid did not prolong the longevity of inflorescences or influence 1-aminocyclopropane-1-carboxylic acid concentrations. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Saks et al (1992) 97 showed that exogenous application of gibberellic acid delayed the senescence of cut carnation flowers with reduced ethylene production. Recently, Setyadjit et al (2006) 98 treated an ethylene-sensitive flower Grevillea 'Sylvia' and this treatment did not enhance the longevity of inflorescences and ACC level. At higher level gibberellic acid concentrations enhanced flower abscission rather than senescence.…”
Section: Hormonal Regulation Of Flower/petal Senescencementioning
confidence: 98%
“…Saks et al (1992) 97 showed that exogenous application of gibberellic acid delayed the senescence of cut carnation flowers with reduced ethylene production. Recently, Setyadjit et al (2006) 98 treated an ethylene-sensitive flower Grevillea 'Sylvia' and this treatment did not enhance the longevity of inflorescences and ACC level. At higher level gibberellic acid concentrations enhanced flower abscission rather than senescence.…”
Section: Hormonal Regulation Of Flower/petal Senescencementioning
confidence: 98%
“…Gibberellic acid is known to delay senescence in some cut carnation flowers by acting as an antagonist to ethylene (Saks et al, 1992;Saks and & Staden, 1993). In Grevillea, higher levels of gibberellic acid was found to enhance flower abscission rather than senescence (Setyadjit et al, 2006), but the treatment did not enhance the longevity of inflorescences as also the ACC level.…”
Section: Involvement Of Hormones (Other Than Ethylene) In Ethylene-sementioning
confidence: 98%
“…However, 1-methylcyclopropene had no effect in the absence of exogenous ethylene. The longevity of cut Grevillea 'Sylvia' inflorescences was extended by dipping them in a solution of 6-benzylaminopurine (Setyadjit et al, 2004b), but vase solutions containing gibberellic acid did not affect vase-life (Setyadjit et al, 2006).…”
Section: Discussionmentioning
confidence: 99%